2021
DOI: 10.1007/s00421-021-04657-w
|View full text |Cite
|
Sign up to set email alerts
|

Non-local acute stretching effects on strength performance in healthy young adults

Abstract: Background: Static stretching (SS) can impair performance and increase range of motion of a nonexercised or non-stretched muscle respectively. An underdeveloped research area is the effect of unilateral stretching on non-local force output.Objective: The objective of this review was to describe the effects of unilateral SS on contralateral, non-stretched, muscle force and identify gaps in the literature.Methods: A systematic literature search following Preferred Reporting Items for Systematic Review and Meta-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The differences in results can possibly be attributed to non-unified stretching protocols and/or measuring devices as well as differences in stretch intensity and duration (Kay & Blazevich, 2012). An acute negative impact on MSt-described as a stretchinduced force deficit (Behm, Alizadeh, Drury, Granacher, & Moran, 2021;Costa, Herda, Herda, & Cramer, 2014)-were only reported for stretching duration of > 45 s (Kay & Blazevich, 2012;Simic, Sarabon, & Markovic, 2013). No negative influence on MSt was found for shorter stretching durations.…”
Section: Introductionmentioning
confidence: 93%
“…The differences in results can possibly be attributed to non-unified stretching protocols and/or measuring devices as well as differences in stretch intensity and duration (Kay & Blazevich, 2012). An acute negative impact on MSt-described as a stretchinduced force deficit (Behm, Alizadeh, Drury, Granacher, & Moran, 2021;Costa, Herda, Herda, & Cramer, 2014)-were only reported for stretching duration of > 45 s (Kay & Blazevich, 2012;Simic, Sarabon, & Markovic, 2013). No negative influence on MSt was found for shorter stretching durations.…”
Section: Introductionmentioning
confidence: 93%
“…When considering unilateral stretching, one study reported that, besides the decrease in strength of the ipsilateral limb (− 6.7%; ES = 0.35), strength also decreased in the contralateral limb (− 4.0%; ES = 0.22), but with a small magnitude of change (Behm et al 2021c ). Since a favorable warm-up effect of FR over stretching on performance parameters exists, at least for the ipsilateral limb (Konrad et al 2021 ), the decrease after stretching in the contralateral limb (Behm et al 2021c ) and the almost no change in performance in the contralateral limb after FR seen in our analysis seems to be coherent with the stretching literature.…”
Section: Contralateral Effects Of Foam Rolling On Performance Parametersmentioning
confidence: 99%
“…The investigator helped the participant towards the maximum tolerable trunk flexion angle and maintained the participant’s position for the duration of the planned stretch by positioning his hands on the lower back of the participant. This protocol was chosen since it is frequently adopted in studies evaluating the acute effects of stretching [ 47 ].…”
Section: Methodsmentioning
confidence: 99%